Language Policy in Teaching STEM in Morocco: Teachers’ Perspective of Using French in Moroccan STEM classes (Jurnal Sustainable, 2023)
This chapter is an exploratory study of the effect of changing language policy on students and teachers in studying/teaching STEM (Science, Technology, Engineering, and Mathematics) in Arabic language to French. It examines the challenges they both face in the use of a foreign language in academic, personal, and social levels, taking into considerations various factors of gender, education, and social status. This investigation goes beyond the political struggles and ideologies to shed light on those directly affected by these changes; students and teachers. The program started in 2014-2015; almost a decade has passed since its launch, providing teachers with more than enough time to accumulate insight into the failure or success of this language policy as well as the real challenges facing its implementation.